Data from Population-based Cancer Registration for Secondary Data Analysis: Methodological Challenges and Perspectives - Arndt, Volker; Holleczek, Bernd; Kajüter, Hiltraud; Luttmann, Sabine; Nennecke, Alice; Zeissig, Sylke Ruth; Kraywinkel, Klaus; Katalinic, Alexander (Das Gesundheitswesen, 2020)
Population-based cancer registries have a long-standing role in cancer monitoring. Scientific use of cancer registry data is one important purpose of cancer registration, but use of cancer registry data is not restricted to cancer registries. Cancer registration in Germany is currently heading towards population-based collection of detailed clinical data. This development together with additional options for record linkage and long-term follow-up will offer new opportunities for health services and outcome research. Both regional population-based registries and the German Centre for Cancer Registry Data (ZfKD) at the Robert Koch-Institute as well as international cancer registries and consortia or organizations may provide external researchers access to individual or aggregate level data for secondary data analysis. In this review, we elaborate on the access to cancer registry data for research purposes, availability of specific data items, and options for data linkage with external data sources. We also discuss as well as on limitations in data availability and quality, and describe typical biases in design and analysis.
Keywords: cancer registration; epidemiology; secondary data; data quality; data sources